Arctic cloud properties derived from ground-based sensor synergy at Ny-Ålesund - Nomokonova, Tatiana (2020)
Contemporary climate models show that clouds are one of the key components in the climate of the Arctic region experiencing rapid surface warming. Modeling of the cloud impact on the Arctic amplification is still uncertain not only because cloud life cycle is defined by large number of processes, but also because the clouds are closely related to other components of the Arctic climate, such as atmospheric water vapor, ocean, sea ice, and long-range air transport. In order to better understand the role of clouds in the Arctic, in June 2016 the French-German Arctic research station situated in Ny-Ålesund, Norway was complemented with a W-band cloud radar within the Transregional Collaborative Research Center (TRR 172) "Arctic Amplification: Climate Relevant Atmospheric and Surface Processes, and Feedback Mechanisms (AC)³". This observation site became one of a few Arctic sites capable of state-of-the-art cloud profiling with high temporal and spatial resolution. This thesis summarizes the cloud macro and microphysical properties of clouds based on the first two and a half years of cloud measurements at Ny-Ålesund. The total occurrence of clouds was found to be ~81%. The most predominant type of clouds is multi-layer clouds with the frequency of occurrence of 44.8%. Single-layer clouds occur 36% of the time. The most common type of single-layer clouds is mixed-phase with a frequency of occurrence of 20.6%. The total occurrences of single-layer ice and liquid clouds are 9% and 6.4%, respectively. A comparison of cloud occurrence at Ny-Ålesund with a numerical weather prediction model revealed an overestimation in the occurrence of single layer ice clouds and underestimation of the occurrence of mixed-phase clouds. The cloud properties were further related to occurrence of anomalous atmospheric conditions often caused by transport of relatively warm and moist air from the North Atlantic and circulation of dry and cold air in the Arctic region. Dry anomalies are related to about 30% less cloud occurrence with respect ...